2020
DOI: 10.1002/aur.2448
|View full text |Cite
|
Sign up to set email alerts
|

Attend Less, Fear More: Elevated Distress to Social Threat in Toddlers With Autism Spectrum Disorder

Abstract: Differential emotional reactivity to social and nonsocial stimuli has been hypothesized but rarely examined empirically in ASD despite its potential importance for development of social motivation, cognition, and comorbid psychopathology. This study examined emotional reactivity, regulation, and attention to social and nonsocial threat in toddlers with ASD (n = 42, Mage: 22 months) and typically developing (TD) toddlers (n = 22, Mage: 23 months), and their mutual associations with autism symptom severity. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…For example, Macari et al (2018) also did not find group differences during bubbles and reported increased levels of negative affect in toddlers with ASD during tasks that included masks as a part of the testing protocol (fear protocol). In addition, children with ASD in the Macari et al (2021) study spent less time looking at distressing stimuli and displayed increased levels of distress compared to their neurotypical peers. Increases in displayed negative affect and reduced gaze during distressing stimuli may reflect atypical regulation and/or expression of negative emotions, potentially affecting early social interactions and contributing to the early presentation of ASD.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Macari et al (2018) also did not find group differences during bubbles and reported increased levels of negative affect in toddlers with ASD during tasks that included masks as a part of the testing protocol (fear protocol). In addition, children with ASD in the Macari et al (2021) study spent less time looking at distressing stimuli and displayed increased levels of distress compared to their neurotypical peers. Increases in displayed negative affect and reduced gaze during distressing stimuli may reflect atypical regulation and/or expression of negative emotions, potentially affecting early social interactions and contributing to the early presentation of ASD.…”
Section: Discussionmentioning
confidence: 94%
“…People, particularly unfamiliar people, could also have the potential to be over-arousing and anxiety-producing in autism. Recent research by Macari et al (2020) suggests that autistic children display diminished attention and enhanced distress toward a novel, or unfamiliar person from toddlerhood on, in contrast to other studies documenting normative arousal in response to eye contact with familiar people (Nuske et al, 2014(Nuske et al, , 2015Vivanti & Nuske, 2017). This suggests that emotional responses to social stimuli are mediated by the familiarity of the situation in the autistic population.…”
Section: Emotional/motivational Processesmentioning
confidence: 91%
“…Some researchers create and use their databases despite the comprehensive databases, which are sometimes too small to reach high statistical power. That fact might limit the conclusions drawn from the results (Norcia et al, 2021) (Macari et al, 2021).…”
Section: Spark (Simons Foundation Powering Autism Research For Knowle...mentioning
confidence: 97%
“…Sometimes, they also consider the ASD group as homogeneous concerning the chosen aspect of their research (Macari et al, 2021). In reality, some characteristics of TD individuals and ASD subgroups might overlap (Kim et al, 2018), different causes might lead to the same symptoms (Constantino & Charman, 2016), and the combination of ASD symptoms that occur in one individual may be caused by several different mechanisms (Katuwal et al, 2016).…”
Section: Figure 7 Model Types and Possible Subgroups Based On The Pur...mentioning
confidence: 99%